When Our Words Return - Schneider , William (Utah State University, University Libraries, 1995)
The title to this interdisciplinary collection draws on the Yupik Eskimo belief that seals, fish, and other game are precious gifts that, when treated with respect and care, will return to be hunted again. Just so, if oral traditions are told faithfully and respectfully, they will return to benefit future generations. The contributors to this volume are concerned with the interpretation and representation of oral narrative and how it is shaped by its audience and the time, place, and cultural context of the narration. Thus, oral traditions are understood as a series of dialogues between tradition bearers and their listeners, including those who record, write, and interpret.